ANALISIS D-DIMER DAN CRP PADA PASIEN COVID-19 DENGAN KOMORBID DIABETES MELLITUS - Warida Daulay; Citra Amaniah Anhar; Adik Purnama (Meditory : The Journal of Medical Laboratory, 2023)
Background:Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2) is a virus that attacks and causes respiratory problems. Patients with comorbid diabetes mellitus are in the high-risk category if they get infected with COVID-19, with a 50% risk of death compared to those without diabetes mellitus. In Covid-19 patients, coagulation disorders are often found, and D-Dimer examination and CRP levels for inflammatory processes must bechecked to assess the continuity of the coagulation process. Aims:This research aims to analyze D-dimer and CRP levels in confirmed Covid-19 patients with comorbid diabetes mellitus at the Jakarta Haji Hospital. Methods:The research is a cross-sectional research design. Data was taken from medical records of patients aged over 25 years who were treated with confirmed Covid-19 with comorbid diabetes mellitus at the Jakarta Haji Hospital for the period June 2021-September 2021 and obtained data for 80 people. Results:Patient characteristics for this research in the majority age group came from adults (25-55 years), as many as 45 people (56%), the sex group of the majority of male patients totalling 44 people (55%), and Blood Glucose Levels during with the largest group in the group that has levels of 200 300 mg/dl of 57 people (71%). Analysis of D-Dimer levels showed that 50 people (63%) had high values ( 5 ng/mL), while CRP levels showed that 55 people (69%) had high values ( 60 mg/dL). Conclusion:COVID-19 patients with comorbid Diabetes Mellitus have increased levels of D-Dimer and CRP with mean results are 7.0 ng/mL and 68.5 mg/dL.